2015
DOI: 10.1016/j.toxrep.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent effects of developmental arsenic exposure on methylation capacity and methylation regulation of the glucocorticoid receptor system in the embryonic mouse brain

Abstract: Previously we have shown that prenatal moderate arsenic exposure (50 ppb) disrupts glucocorticoid receptor (GR) programming and that these changes continue into adolescence in males. However, it was not clear what the molecular mechanisms were promoting these GR programming changes or if these changes occurred in arsenic-exposed females. In the present studies, we assessed the effects of arsenic on protein and mRNA of the glucocorticoid receptor (GR) and 11β-hydroxysteroid dehydrogenase (Hsd) isozymes and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 52 publications
2
17
2
Order By: Relevance
“…Epidemiological studies on the impact of arsenic on cognitive development in children demonstrate a significant sex difference, with females protected against arsenic’s effects ( Rosado et al, 2007 ; Tyler and Allan, 2014 ). Indeed, we have observed a resilience to arsenic exposure in the female brain counter to findings in the male brain, especially with regard to epigenetic mechanisms of action ( Allan et al, 2015 ; Tyler et al, 2015a , 2017 ). However, it is unclear if this arsenic-induced sex difference manifests as differences in behavioral flexibility, which, in part, underlies neurodegeneration.…”
Section: Introductioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Epidemiological studies on the impact of arsenic on cognitive development in children demonstrate a significant sex difference, with females protected against arsenic’s effects ( Rosado et al, 2007 ; Tyler and Allan, 2014 ). Indeed, we have observed a resilience to arsenic exposure in the female brain counter to findings in the male brain, especially with regard to epigenetic mechanisms of action ( Allan et al, 2015 ; Tyler et al, 2015a , 2017 ). However, it is unclear if this arsenic-induced sex difference manifests as differences in behavioral flexibility, which, in part, underlies neurodegeneration.…”
Section: Introductioncontrasting
confidence: 75%
“…We have demonstrated arsenic’s impact on development of the brain, including effects on molecular pathways controlling neural stem cell differentiation that may propagate into aberrant hippocampal functioning in adulthood. We have proposed that the toxic mechanism of action of this heavy metal, particularly in the brain and among the sexes, is initiated via altered epigenetic processes ( Allan et al, 2015 ; Tyler et al, 2015b , 2017 ) and thus has the potential to be corrected using epigenetic modifiers. In the present study, we tested the hypothesis that aberrant executive functioning induced by DAE is ameliorated by administration of an epigenetic modifier and that these deficits are apparent in male but not female mice.…”
Section: Discussionmentioning
confidence: 99%
“…No sex patterning in methylation was observed for As, Cd, or Hg. Previous work has shown some epigenetic patterning by sex in relation to prenatal As, Cd, and Pb exposures and DNA methylation, 26,40,50,51 though these studies reflect a heterogeneous mix of epigenome wide association studies, candidate gene examinations, and mouse models, rendering it difficult to compare our findings with published research. Thus, we suggest cautious interpretation of our sex-specific analysis and advise replication of these results.…”
Section: Discussionmentioning
confidence: 77%
“…No human studies have considered the role of neurotoxic metals as similarly disrupting NR3C1, despite the evidence linking prenatal metals exposure to a similar set of at-risk neurobehavioral phenotypes. Emerging animal work finds that prenatal arsenic exposure is associated with less Nr3c1 expression, 39 and lower levels of Nr3c1 methylation in mouse brains, 40 suggesting prenatal programming to the glucocorticoid system may be attributable in part to arsenic exposure. Among humans, 2 recent studies of pregnant women found that lead, 41 and mercury in association with psychosocial stress, 42 were concurrently associated with dysregulated maternal salivary cortisol, suggesting heavy metals may disrupt HPA function during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that a differential response of females to environmentally-relevant arsenic exposure is not novel and therefore expected [57]. We have previously demonstrated sex-dependent effects of prenatal arsenic exposure in the embryonic and adult brain [3,59]. These data further confirm that while the female brain seems to be susceptible to arsenic exposure during the embryonic period, by adulthood, the female brain is protected, signifying a lack of prenatal programming [59].…”
Section: Discussionmentioning
confidence: 99%